Towards the construction of a social history of Freemasonry in Central America - Martínez Esquivel, Ricardo (2013)
Masonic Latin American historiography is undergoing a methodological regeneration therefore it is necessary performing a state of matter. This paper is divided into four parts. The first one synthesizes historiographical renewal on Freemasonry studies. The following examines the writing so far on Freemasonry in Central America, not including itself because it is considered to correspond to other do it. The third part analyzes the main results of the research on the Masonic issue and proposes a series of new problems that could be researched. And the final part refers to the first section in the bibliography, which includes all it has been written about Freemasonry in Central America. It must be emphasized that is an open whose completeness is as complex as the theme itself. Therefore, just wants to be a point of reference on completing this historiography will continue in the future.